Examining the Impact of Waqf Literacy on Waqf Behaviour - Nashr Akbar; Salina Hj. Kassim; Fahd Mohammed Obad Al-Shaghdari; Irfan Syauqi Beik (Journal of Islamic Monetary Economics and Finance, 2026)
This paper investigates the impact of waqf literacy on waqf donation of Muslims in Indonesia. It applies the Partial Least Square - Structural Equation Modeling (PLS-SEM) to data from 642 respondents. Using the Theory of Planned Behaviour (TPB) framework extended to past behaviour as an additional component, we find that waqf literacy positively impacts attitude, social norms, perceived behavioural control (PBC), and past behaviour. In addition, it has an indirect influence on waqf intention through those four TPB components. Moreover, the non-linearity test finds the quadratic effect of waqf literacy on most TPB components. This finding shows significant contribution of Waqf literacy on Muslims’ waqf donation indirectly through the Theory of Planned Behaviour. As a result, all waqf stakeholders should pay more attention toward waqf literacy in order to boost waqf collection.